2008
DOI: 10.1375/twin.11.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Self-Reported Asthma and Allergy: A Study in Adult Dutch Twins, Siblings and Parents

Abstract: The present study assessed the prevalence of asthma and allergy, and estimated the importance of genetic and environmental influences on asthma and allergy liability and their association. Longitudinal data on self-reported, doctor-diagnosed asthma and allergy were collected in over 14,000 individuals registered with the Netherlands Twin Register. Structural equation modeling was used for univariate and bivariate genetic analyses on data from twins, their siblings, and parents. Results showed no sex, age, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 36 publications
1
58
0
2
Order By: Relevance
“…Multiple factors play a role in the development of asthma and the exacerbation of asthma symptoms. It is believed that genetic predisposition, exposure to environmental factors, and significant gene-environment interactions may influence development of asthma and exacerbation of the symptoms (6)(7)(8)(9)(10)(11). Genetic predisposition may lead to the development of asthma and allergies (e.g., atopic dermatitis [eczema] or allergic rhinitis [hay fever]) (6,8).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple factors play a role in the development of asthma and the exacerbation of asthma symptoms. It is believed that genetic predisposition, exposure to environmental factors, and significant gene-environment interactions may influence development of asthma and exacerbation of the symptoms (6)(7)(8)(9)(10)(11). Genetic predisposition may lead to the development of asthma and allergies (e.g., atopic dermatitis [eczema] or allergic rhinitis [hay fever]) (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that genetic predisposition, exposure to environmental factors, and significant gene-environment interactions may influence development of asthma and exacerbation of the symptoms (6)(7)(8)(9)(10)(11). Genetic predisposition may lead to the development of asthma and allergies (e.g., atopic dermatitis [eczema] or allergic rhinitis [hay fever]) (6,8). However, the genotype of asthma is complex (10,11) and a positive family history of asthma does not always predict the disease's development (9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that asthma is one of the most serious allergic diseases and the most common child and adolescent disease in developed countries (13 susceptibility genes, their locations and possible correlations with asthma in specific populations. Different genes may be involved in the pathogenesis of asthma, explaining the possibility of different outcomes amongst affected individuals (14,15). The complexity of the immunological network involved in the demonstration of the complete linkage of genes and asthma remain a barrier in understanding the aetiology, pathophysiology and management of asthma (16).…”
Section: Resultsmentioning
confidence: 99%